Towards digital twinning of electrical motors – simulation models - Kurtović, Goran (Journal of energy technology, 2025)
This paper presents a methodological framework for building a digital shadow of an induction motor based on standardised tests and a two-axis (dq) simulation model. The tests were carried out according to IEEE Std 112 and IEC 60034-2-1. The parameters of the equivalent circuit were identified and entered into the model. Validation was performed by comparing the torque–speed and current–speed curves at 180 V and 220 V, while the nominal behaviour at 400 V was estimated using the model and voltage scaling. The model was then calibrated to reduce the discrepancy between the simulation and measurements, and the error was quantified using the root-mean-square error (RMSE) and mean absolute percentage error (MAPE). An automated load-simulation setup that reproduces the torque test is also presented, enabling rapid evaluation of parameter influence. The results show a very good match in the current channel, with larger deviations in the prediction of characteristic torque points, indicating the limitations of linearised parameters and motivating nonlinear model extensions. The approach enables summarised reliable estimates at nominal voltage when direct measurements are not feasible.
Keywords: automated load simulation; digital shadow; dq model; induction motor; model calibration; standardised tests; torque test